2019
DOI: 10.1097/jnr.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Problem-Solving Skills and Empathy Skills of Operating Room Nurses

Abstract: Background The use of empathy in problem solving and communication is a focus of nursing practice and is of great significance in raising the quality of patient care. Purpose The purposes of this study are to investigate the relationship between problem solving and empathy among operating room nurses and to explore the factors that relate to these two competencies. Methods This is a cross-sectional, descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Parents therefore develop higher levels of empathy. Despite that, a similar study in operating room nurses in Turkey demonstrated contradictory evidence, by highlighting no correlation between marital status and levels of empathy [30].…”
Section: Empathymentioning
confidence: 96%
See 1 more Smart Citation
“…Parents therefore develop higher levels of empathy. Despite that, a similar study in operating room nurses in Turkey demonstrated contradictory evidence, by highlighting no correlation between marital status and levels of empathy [30].…”
Section: Empathymentioning
confidence: 96%
“…Another important finding is that HCAs demonstrated higher empathy levels compared to staff nurses. This might be related to the educational level, as relevant research [30], stressed that when the level of education increases, cognitive and emotional levels of empathy decrease. It should also be noticed that in the present study, the in-hospital work system involves the performance of many tasks by HCAs demanding more frequent and intense communication with patients.…”
Section: Empathymentioning
confidence: 99%
“…Research shows that the concept of emotional empathy is state empathy, with the focus on altruism [ 83 , 84 ]. Emotional empathy plays an important role in patient-nurse communication [ 85 ]. Failure to deal with or understand emotions will make it difficult for nurses to think rationally and critically about issues that are important to nursing practice [ 86 ].…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…In today’s complex clinical environment, nurses need to be able to solve problems accurately, thoroughly, and quickly. Nurses who can solve problems efficiently have fewer medical errors (Babaei et al, 2018 ), and the level of nursing skills and empathy are higher (Ay et al, 2020 ; Bayindir Çevik & Olgun, 2015 ). To cultivate nurses’ problem solving thinking and ability, it is necessary to better understand the influencing factors of problem solving dilemma.…”
Section: Introductionmentioning
confidence: 99%